Empirical Estimate for the Element Number of a Nonredundant Configuration on a Hexagonal Telescope Aperture - Kopilovich, L.E. (Радиофизика и радиоастрономия, 2006)
The empirical upper estimate is obtained for the number of elements of a nonredundant configuration on a given size hexagonal telescope aperture. Nonredundancy means that all the differences between vector radii of the configuration elements (“vector differences”) are distinct. The suggested estimate agrees well with the data available and can serve as a guiding line in evaluation of the maximum element number of a large-order nonredundant configuration.